Formative Research in Peruvian Universities: Analysis of Trends and Challenges in Institutional Documents (Revista Lusófona de Educação, 2025)
Historically, Peruvian universities have had low levels of research productivity. As a result, educational policies aimed at improving this aspect have been presented, among them, the enhancement of the value of the research produced in these houses of study. However, it is necessary to train researchers with effective strategies, such as formative research (FR). Although the situation in terms of research seems to be improving in recent years, it is necessary to evaluate the current state of FI in these institutions. Therefore, the objective of this study was to review the situation of formative research in Peruvian universities. For this purpose, a documentary review of the documents guiding the educational offerings was used. The findings reveal that FI is more present in public than in private universities. On the other hand, it is mainly considered in educational models and institutional strategic plans. In addition, there is evidence of a diversity of forms of consideration of FI in the documents. Finally, it was identified that the main reason for universities not considering FI is that there is no record of it in management documents. In the absence of previous similar studies, the results are discussed with specific evidence for each objective. The limitations of the work and future lines of research are also presented.